A Comparative Literature of Reader Response Theory in Thriller Fictions: Sheldon vs. Ramlee - Mohd Nazri, Latiff Azmi; Mairas, Abd. Rahman; Mohamad Farza, - (2013)
This comparative literature study focuses on the elements of Reader Response Theory (RRT) in thriller fictions between two outstanding American and Malaysian novelists, Sidney Sheldon and Ramlee Awang Murshid. Sheldon, one of the most famous American authors who wrote a lot of magnificent novels, whereas Ramlee is an established thriller fiction novelist in Malaysia. According to International Thriller Writers, a thriller is characterized by "the sudden rush of emotions, the excitement, and sense of suspense, apprehension, and exhilaration that drive the narrative, sometimes subtly with peaks and lulls, sometimes at a constant, breakneck pace." Therefore, this qualitative study aims to find the similarities and differences of both popular novelists from the view of RRT and how they managed to attract readers. From other point of views, the study also stresses on the elements of the concepts of “meaning” and “truth” in their literary works, in which are the main attractions to their avid readers and followers. Based on the findings, it is obvious that both authors implement different styles and figurative language to capture reader’s thriller mood, in which it is extremely successful.